Sociology on the menu : an invitation to the study of food and society - Beardsworth, Alan, 1945-; Keil, Teresa, 1935- (Routledge, 1997)
Sociology on the Menu is an accessible introduction to the sociology of food. Highlighting the social and cultural dimensions of the human food system it encourages us to consider new ways of thinking of the everyday act of eating.